A conceptual framework for a (RE-) assessment of small-scale fishermen vulnerability / Nor Samsinar Kamsi, Dr. Radin Firdaus Radin Badaruddin and Akmal, S. M. - Kamsi, Nor Samsinar; Radin Badaruddin, Dr. Radin Firdaus; M., Akmal, S. (2021)
In Malaysia and elsewhere, vulnerability and poverty among small-scale fishermen are important issues. In a reality check, there are still many of them earn income range between RM300 to RM2000 ((Lili Maisara et al., 2019; Ramli et al., 2019; Solaymani & Kari, 2014). Even after the poverty line income (PLI) was revisited in 2019, the average income for the small-scale fishermen is still fell below the national PLI of RM2,208.00 (DOSM, 2020). Nonetheless, vulnerability can be assessed in any setting that corresponds to a particular scale or community. Notably, the national inflation rate of foods from 2018 to 2019 across selected food subgroups increased substantially (DOSM, 2019). According to Maslow's hierarchy, the degree of severity increases when a household is unable to meet basic needs. In the context of food security, vulnerability is frequently described in terms of a consequence such as hunger, food insecurity, or famine. According to the Food and Agriculture Organization’s (FAO) food security concept framework, the vulnerability will be quantified in this study by identifying loci and domains of food security that are susceptible to damage when exposed to various hazards or shocks. The notion of adaptive capacity (livelihood assets) about exposure (natural risk, environmental risk, social risk, and health risk) and sensitivity (food availability, food accessibility, food usage, and food stability) is used to analyse the vulnerability of small-scale fishers. By conducting a comprehensive examination of the food security concepts that operate within the vulnerability framework, this study can shed light on the vulnerability condition affecting small-scale fishing households.